Rise in pneumonia cases of unknown aetiology in Kazakhstan in June 2020: a rapid analysis - Phi-Yen Nguyen; Xin Jessie Chen; Mohana Kunasekaran (University of New South Wales, 2020)
On 09 July 2020, the Chinese Embassy in Kazakhstan issued warning of a "local pneumonia of unknown cause" in Kazakhstan, which purportedly had a much higher fatality rate than COVID-19. The Ministry of Health of Kazakhstan refuted the claim, stating that these pneumonia cases diagnosed clinically without laboratory confirmation, and might include non-laboratory confirmed COVID-19 cases. This article aims to provide a rapid epidemiological analysis of pneumonia and COVID-19 in Kazakhstan from January-June 2020 and examine past trends in respiratory disease outbreaks in Kazakhstan since September 2019. Descriptive statistics were presented using COVID-19 statistics from World Health Organisation (WHO) and pneumonia statistics from media briefings by Kazakhstan's Ministry of Health. Case fatality rates (CFR) of pneumonia cases for the first 6 months of 2019 and 2020 were 2.67% and 1.42%, respectively. CFR of pneumonia cases for June 2019 and June 2020 were 3.44% and 1.92%, respectively. The number of pneumonia cases and deaths have increased in 2020, but with lower CFR, as compared to the same period in 2019. From 16 September 2019 to 10 July 2020, a total of 80 reports of disease outbreaks in Kazakhstan were detected, including 15 reports of respiratory diseases of unknown aetiology. A cluster of 6 reports were detected over 2 days about the surge in pneumonia cases in June 2020, a strong signal that prompted the investigation underlying this study.